Perencaaan dan Kebijakan Ekonomi Nabi Yusuf As - Nasyiatul Aisyah (IAIN Batusangkar, 2021)
To build a good economic system, various kinds of policies related to the economy were born, both conventional economic policies and sharia policies. Prophet Yusuf as a Prophet and Messenger of Allah during his leadership in Egypt has established a very accurate economic system, which is of course under the guidance of Allah's revelation. Reflecting on the success of the Prophet Yusuf, this research is a literature study that tries to reveal how the economic policies implemented by the Prophet Yusuf, so that Egypt at that time was able to go through long periods of crisis. From the research, it was found that in economic planning, Prophet Yusuf implemented four things, namely increasing production, frugality or saving, building food barns, and preparing the facilities needed for the recovery period. Economic Law, The Debtor Must Pay, and the Implementation of Penalties for Thieves.